Are positive goals desirable and negative ones painful? : strategic approach and avoidance goal-setting in the academic context. - Tan, Ser Hong. (2010)
Regulatory focus theory distinguishes between promotion goals, defined by progress or lack thereof to desired end-states, and prevention goals, defined by deficits or mismatches to desired end-states. In Study 1 (N = 320), a measure of goals incorporating promotion-prevention motivations with approach-avoidance orientations was developed. This measure was used in Study 2 (N = 75) with multiple assessments of perceived stress and everyday academic resilience administered over 4 weeks leading to examinations. Results showed that higher promotion-avoidance goals predicted higher cumulative perceived stress which in turn predicted lower cumulative everyday academic resilience. Conversely, higher prevention-approach goals predicted lower cumulative perceived stress which in turn predicted higher cumulative everyday academic resilience. Implications for motivation in the academic context are discussed.